(3eONd MOjK dEOGQI GdehGOs - (3eMeO(B, (3GdYOhGfs ((3YeGf(B:s (3OGQ GdUaGA ddfTQ hGdJhRjY(B,s, 2005)
(3GdeaGgje GdCSGSjI dEOGQI GdTQGA (B-(3GdCUhd GdYdejI dEOGQI GdTQGA (B-(3JNWjW GdTQGA (B-(3JfajP GdTQGA (B-(3Jbjje GdTQGA (B-(3JNWjW GdeNRhf (B-(3ELQGAGJ GdJNRjf (B-(3GdQbGHI Ydi GdeNRhfs
(3GdeQGLY U(B. 254s
Keywords: (3EOGQI GdeNGRfs; (3GdTQGAs